Business Process Analysis and Implementation of Odoo ERP in Sales, Purchasing and Accounting Systems (Case Study: CV Mitra Perkasa) : Analisis Proses Bisnis dan Penerapan ERP Odoo pada Sistem Penjualan, Pembelian dan Akuntansi Studi Kasus CV. Mitra Perkasa - Aditya, Addin; Hadi Santuso, Yohanes Eko (Universitas Muhammadiyah Sidoarjo, 2022)
The development of information technology is a major element in business world. Phenomena of using information technology in company is an important element to increase effectiveness and efficiency of business processes. The purpose of this research is to identify business processes related to Sales and Finance & Accounting and company needs using BPMN, and to implement Odoo ERP software which is required by CV. Mitra Perkasa. The model used to analyze current business processes is Value Chain Analysis. This model consists of collection of activities or business processes that occur to create value and competitive advantage for this company. Management system used to integrate business processes in this company is Odoo, which is an open source ERP software that suitable for conditions of a new company, and certainly can reduce costs for the application development process. Method used for testing the application in this research is Conference Room Pilot. The purpose of CRP process is to validate ERP software that has been configured against current business processes. Conclusion of this research show that after a series of demos with business process scenarios, the Odoo ERP system has been adapted to business conditions and can be accepted by CV. Mitra Perkasa.